(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Pleistocene Madhupur Clay covers mostly the investigated region including Dhaka and the surrounding area (Savar). Without knowing the consolidation characteristics and settlement of this Clay, it is difficult for any construction sites to build infrastructure. In Bangladesh, the research on this parameter is limited hence for better understanding the consolidation and settlement behavior of Madhupur Clay samples in this area, a detail investigation is carried out by conducting one dimensional consolidation test. The undisturbed samples, Pleistocene Madhupur Clay and the fill materials which are also partly composed of the Madhupur Clay, are collected from 2.4 m to 4.11 m depths of many distinct points. The compression index Cc and coefficient of compressibility, av of the samples are range from 0.073 to 0.23 and from 0.059 to 0.14m2/mn respectively. The values recommend that both types of specimens are medium plastic clay. The Madhupur Clay are stiff consolidated clay and slightly compressible in nature whereas the Madhupur Clay fill samples are less stiff over consolidated and moderately compressible in nature. Fill samples are settled more with time and are not suitable for Shallow foundation of light or heavy infrastructure. However, the Madhupur Clay samples are only appropriate for light infrastructure foundation. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 27-39